Mechanobiology of Periodontal Ligament Stem Cells in Orthodontic Tooth Movement - Huaming Huang; Ruili Yang; Yan-heng Zhou (Stem Cells International)
Periodontal ligament stem cells (PDLSCs) possess self-renewal, multilineage differentiation, and immunomodulatory properties. They play a crucial role in maintaining periodontal homeostasis and also participated in orthodontic tooth movement (OTM). Various studies have applied controlled mechanical stimulation to PDLSCs and investigated the effects of orthodontic force on PDLSCs. Physical stimuli can regulate the proliferation and differentiation of PDLSCs. During the past decade, a variety of studies has demonstrated that applied forces can activate different signaling pathways in PDLSCs, including MAPK, TGF-β/Smad, and Wnt/β-catenin pathways. Besides, recent advances have highlighted the critical role of orthodontic force in PDLSC fate through mediators, such as IL-11, CTHRC1, miR-21, and H2S. This perspective review critically discusses the PDLSC fate to physical force in vitro and orthodontic force in vivo, as well as the underlying molecular mechanism involved in OTM.